Use of Earthen Materials in Interior Spaces - Ritika Omar; Deepti Pande Rana (International Journal of Architectural Design and Planning, 2024)
This research paper investigates the utilization of earthen materials within interior spaces, focusing on their sustainable attributes and aesthetic potential. In the context of contemporary design practices, there is a growing interest in integrating natural materials that offer environmental benefits and promote well-being. Earthen materials, including clay, adobe, terracotta, and rammed earth, present promising opportunities for sustainable interior design solutions. The research begins by examining the historical and cultural significance of earthen architecture and its evolution through time. Drawing upon case studies from various regions around the world, the research paper highlights the versatility and adaptability of earthen materials in diverse climates and contexts. The study explores the physical properties and environmental characteristics of earthen materials, such as their thermal mass, breathability, and low embodied energy. These attributes contribute to improved indoor air quality, energy efficiency, and overall comfort within interior spaces. Through a review of contemporary design projects and innovative applications, the dissertation showcases the creative potential of earthen materials in interior design. From textured wall finishes to handcrafted furniture and lighting fixtures, earthen elements add warmth, texture, and visual interest to interior environments. The dissertation discusses the implications of using earthen materials from a sustainable design perspective, considering factors such as material sourcing, life cycle analysis, and cultural preservation. By embracing earthen materials in interior design, designers and architects can contribute to the promotion of sustainable lifestyles and the conservation of natural resources. This research underscores the importance of re evaluating traditional building practices and embracing alternative materials such as earthen compounds to foster sustainable design solutions. By leveraging the inherent qualities of earthen materials, designers can not only create aesthetically pleasing and culturally rich interior spaces but also contribute to the broader goal of promoting environmental stewardship and resilience in the built environment.
Keywords: Earthen construction; Environmental impact; Thermal properties; cob construction; construction techniques; earthen plasters; rammed earth; sustainable building